Impact of the Pandemic on the Development of the Ukrainian Insurance Market (Economics and region, 2021)
Based on the generalization of functioning features and insurance market importance in the financial system of the country it was proved that insurance services play an important role in risk management, savings distribution and capital market growth in modern conditions of numerous challenges, risks and threats. It proved that the level of Ukraine’s insurance market development is low compared to other countries in the world in key indicators (penetration and density of insurance), but its growth rate is high. The comparative and trend analysis of the insurance market development indicators was carried out. It was revealed positive dynamics on the main indicators, despite the decrease in activity on travel, aviation and property insurance. Instead, there was a growing demand for compulsory insurance products, which occupies the largest share in the structure of collected insurance premiums in the Ukrainian insurance market. The specifics of the pandemic impact on the insurance market, which is manifested in the stimulation of certain sectors and the emergence of new insurance products, have been studied. It was established that for the insurance market, unlike other areas of the national economy, the pandemic is a driver of development, as the growing level of risk in personal insurance contributes to increasing demand for health insurance products. It was revealed the insurance programs diversification, the insurance field expansion, an increase in the number of policyholders and concluded insurance contracts, in particular in health insurance, the increase in the volume of collected insurance premiums, as well as the digitalization of insurance services provision through the registration of electronic insurance policies, the introduction of client-oriented business models, which contributes to the insurance market development. The financial results of insurance companies in Ukraine were considered. It was identified that their growth rates are the highest among all non-bank financial institutions in a pandemic. The directions of the Ukraine insurance market development in the conditions of epidemic danger based on innovative decisions development and diversification of activity in response to emergence of new risks were defined.
Keywords: insurance market; pandemic; epidemic danger; challenges; risks; dangers; directions of development